Isoxazolidine Derivatives Exhibit Selective Antitumor Activity Against Breast Cancer Cells: Turunan Isoxazolidine Menunjukkan Aktivitas Antitumor Selektif Terhadap Sel Kanker Payudara - Wijdan Abbas Eneama; Husam Hamza Salman; Mazin N`adhim Mousa (Academia Open, 2024)
Breast cancer, a leading cause of cancer-related mortality in women, necessitates effective therapeutic interventions. Heterocyclic compounds, prevalent in FDA-approved pharmaceuticals, play a pivotal role in drug development. This study focuses on isoxazolidine derivatives, a subgroup of nitrogen and oxygen-containing heterocycles, known for their potential in antitumor applications. A series of novel isoxazolidine compounds were synthesized and evaluated for their anticancer efficacy using MTT assays against MCF-7 and HdFn cell lines, alongside normal cells. Structural elucidation employed FT-IR, 13C-NMR, 1H-NMR, and E-I mass spectroscopy. Results revealed compound (IZ3) with an IC50 value of 32.49 µg/ml, demonstrating notable antitumor activity in MCF-7 cells compared to HdFn. Notably, compounds (IZ1 and IZ2) exhibited IC50 values of 64 µg/ml and 128 µg/ml, respectively. These findings underscore the potential of isoxazolidine derivatives as promising candidates for targeted breast cancer therapies, warranting further investigation in preclinical models and clinical trials. Highlight: Novel Isoxazolidine Compounds: Synthesized and Evaluated Selective Antitumor Activity: Demonstrated in MCF-7 Breast Cancer Cells Promising Therapeutic Candidates: Isoxazolidine Derivatives for Targeted Breast Cancer Therapy Keyword: Breast cancer, Isoxazolidine Derivatives, Antitumor Activity, Heterocyclic Compounds, Drug Development